ANALISIS PENERAPAN DISIPLIN SISWA KELAS 1 DI SD SEMESTA SEMARANG DALAM KEGIATAN PEMBELAJARAN - Andita Pertiwi; Riris Setyo Sundari; Veryliana Purnamasari (STKIP Subang, 2026)
This study aims to describe the learning process and analyze the implementation of discipline among first-grade students at SD Semesta Semarang in classroom activities. The research employed a descriptive qualitative approach with research subjects consisting of the principal, two first-grade teachers, and 23 first-grade students. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model including data collection, data reduction, data display, and conclusion drawing. The results showed that the learning process was conducted in an orderly, conducive, interactive, and enjoyable environment. Discipline was implemented through school policies, classroom agreements, teacher role modeling, and a system of rewards and punishments. Most students demonstrated disciplined behavior such as arriving on time, participating in learning activities orderly, and being responsible for assigned tasks. Supporting factors included structured school policies, the teacher’s role as a model, and collaboration with parents, while obstacles were related to students’ characteristics who still require repeated reminders. It can be concluded that the implementation of discipline in first-grade students at SD Semesta Semarang has been carried out effectively and is able to foster orderly, responsible, and rule-abiding behavior in learning activities.